Research Anxiety among Turkish Graduate ELT Students - Ali Merç (Arizona State University, 2016)
The purpose of this study was to investigate the level and predictors of research-related anxiety among graduate ELT students in the Turkish context. 81 MA and PhD students from 14 universities offering graduate programs in ELT responded to a background questionnaire, a research anxiety scale, and a research self-efficacy survey. The analysis of the data revealed that graduate students were moderately anxious about conducting research. It was also found out that self-efficacy beliefs of graduate students were able to explain a certain portion of the research anxiety. Furthermore, while gender and having a publication experience do not affect the level of research anxiety, MA students were found to be having more research-related anxiety than PhD students. Finally, research self-efficacy was found to be negatively correlated with research anxiety. The overall findings suggest that graduate students need support to increase their self-efficacy about research in order to have lower levels of research anxiety. Recommendations for graduate programs and suggestions for further research are also provided.